Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1152/ajpendo.00308.2010
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics analysis reveals diabetic kidney as a ketogenic organ in type 2 diabetes

Abstract: analysis reveals diabetic kidney as a ketogenic organ in type 2 diabetes. Am J Physiol Endocrinol Metab 300: E287-E295, 2011. First published October 19, 2010 doi:10.1152/ajpendo.00308.2010 is the leading cause of end-stage renal disease. To date, the molecular mechanisms of DN remain largely unclear. The present study aimed to identify and characterize novel proteins involved in the development of DN by a proteomic approach. Proteomic analysis revealed that 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) synthase 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 54 publications
(55 reference statements)
2
55
0
Order By: Relevance
“…Anaerobic bacterial fermentation of complex polysaccharides yields butyrate, which is absorbed by colonocytes in mammalians for terminal oxidation or ketogenesis (Cherbuy et al, 1995), which may play a role in colonocyte differentiation (Wang et al, 2016). Excluding gut epithelial cells and hepatocytes, HMGCS2 is nearly absent in almost all other mammalian cells, but the prospect of extrahepatic ketogenesis has been raised in tumor cells, astrocytes of the central nervous system, the kidney, pancreatic β cells, retinal pigment epithelium (RPE), and even in skeletal muscle (Adijanto et al, 2014; Avogaro et al, 1992; El Azzouny et al, 2016; Grabacka et al, 2016; Kang et al, 2015; Le Foll et al, 2014; Nonaka et al, 2016; Takagi et al, 2016a; Thevenet et al, 2016; Zhang et al, 2011). Ectopic HMGCS2 has been observed in tissues that lack net ketogenic capacity (Cook et al, 2016; Wentz et al, 2010), and HMGCS2 exhibits prospective ketogenesis-independent ‘moonlighting’ activities, including within the cell nucleus (Chen et al, 2016; Kostiuk et al, 2010; Meertens et al, 1998).…”
Section: Controversies In Extrahepatic Ketogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Anaerobic bacterial fermentation of complex polysaccharides yields butyrate, which is absorbed by colonocytes in mammalians for terminal oxidation or ketogenesis (Cherbuy et al, 1995), which may play a role in colonocyte differentiation (Wang et al, 2016). Excluding gut epithelial cells and hepatocytes, HMGCS2 is nearly absent in almost all other mammalian cells, but the prospect of extrahepatic ketogenesis has been raised in tumor cells, astrocytes of the central nervous system, the kidney, pancreatic β cells, retinal pigment epithelium (RPE), and even in skeletal muscle (Adijanto et al, 2014; Avogaro et al, 1992; El Azzouny et al, 2016; Grabacka et al, 2016; Kang et al, 2015; Le Foll et al, 2014; Nonaka et al, 2016; Takagi et al, 2016a; Thevenet et al, 2016; Zhang et al, 2011). Ectopic HMGCS2 has been observed in tissues that lack net ketogenic capacity (Cook et al, 2016; Wentz et al, 2010), and HMGCS2 exhibits prospective ketogenesis-independent ‘moonlighting’ activities, including within the cell nucleus (Chen et al, 2016; Kostiuk et al, 2010; Meertens et al, 1998).…”
Section: Controversies In Extrahepatic Ketogenesismentioning
confidence: 99%
“…The authors of a classical study concluded that minimal renal ketogenesis quantified in an artificial experimental system was not physiologically relevant (Weidemann and Krebs, 1969). Recently, renal ketogenesis has been inferred in diabetic and autophagy deficient mouse models, but it is more likely that multi-organ shifts in metabolic homeostasis alter integrative ketone metabolism through inputs on multiple organs (Takagi et al, 2016a; Takagi et al, 2016b; Zhang et al, 2011). One recent publication suggested renal ketogenesis as a protective mechanism against ischemia-reperfusion injury in the kidney (Tran et al, 2016).…”
Section: Controversies In Extrahepatic Ketogenesismentioning
confidence: 99%
“…Most ketone body production occurs in the liver [9], although smaller amounts may be produced in other tissues through aberrant expression of ketogenic enzymes [17, 18] or reversal of the ketolysis pathway [19, 20]. In hepatic ketogenesis (Figure 1), fatty acids are first metabolized to acetyl-CoA via mitochondrial β-oxidation.…”
Section: Metabolism Regulation and Function Of Ketone Bodiesmentioning
confidence: 99%
“…Increased expression of mitochondrial 3-hydroxy-3-methylglutaryl-CoA synthase 2 (HMGCS2) was found using 2-DE analysis in kidney of diabetic mice. It was proposed that excess of ketogenic activity resulting from increased expression of HMGCS2 contributes to diabetic nephropathy and HMGCS2 may therefore represent a potential therapeutic target 85 . Proteomic analysis of cytosolic and mitochondrial fractions of diabetic mice kidney provided data about migration of mitochondrial proteins 86 .…”
Section: Diabetesmentioning
confidence: 99%
“…Proteomic profi le of kidney and identifi cation of mitochondrial ketogenic enzyme 85 . Posttranslational modifi cation of mitochondrial proteome 86,15 .…”
Section: Hypertensionmentioning
confidence: 99%